Determinants of workers' pro-environmental behaviour towards enhancing construction waste management: Contributing to China's circular economy. (1st October 2022) - Hao, Jian Li; Yu, Shiwang; Tang, Xiaonan; Wu, Weiwei
Abstract: Construction waste presents many challenges for sustainable development and ultimately for China's goal of a circular economy. Effective construction waste management (CWM) is necessary to tackle these challenges, the success of which depends in large part on the behaviour of workers. Most previous behavioural research relating to CWM focused on reduction or recycling behaviour, with few studies having examined pro-environmental behaviour (PEB) within organisations. This study therefore conducted research into the key determinants of two types of PEB relating to CWM. A questionnaire survey was conducted on five construction sites in China to identify the critical organisational and personal determinants predicting PEB relating to CWM, including self-enacted PEB and co-worker PEB. One hundred and fifty-two valid questionnaires were collected for data analysis, representing an overall response rate of 30.4%. Results of the analysis reveal that physical stress, environmental awareness, and tedious construction processes are significant predictors of PEB. Based on these results, practical suggestions for enhancing CWM are proposed. The findings of this research could help improve PEB among construction workers and thereby contribute to China's circular economy.